(3GdQSGdI GdceGdjI aj GdMbGFb GdEdgjIs - (3GdJjej, GdHcQj, GdWHQSJGfj, GdQGRj, GdTGaYj, CHh YHO Gddg, GHf NWjH GdQj, aNQ GdOjf, eMeO Hf YeQ Hf GdMSf Hf GdMSjf, (B606 (3g`s ((3YHO GdcQjes)
(3ChdgG (B:s
(3GdMeO ddg (B... (3cd eWdhH cGf CTQa hCHbi jchf HGdWdH CMb hCMQi hGdYde Hjf GdeWGdH cPdc aJchf GdeWdhHjI Cdjb hChab hCTQajI Yde GdEdgj ef Hjf SGFQ GdYdhe ef NeSI GhLg ; GdChd (B: (3Gf eYdheg hehVhYg CTQa GdeYdheGJ hGdehVhYGJ (B...s
(3BNQgG (B:s
... (3hjchf GdaUhd KeGfjI hdG Jchf GdaUhd beGfjI hdG Jchf GdaUhd KeGfjI cPG hdG Jchf Jdc GdaUhd eJSGhjI aj GdeOI Hd Jchf eNJdaI hdeG hUd GdcdGe Gdi gPG GdebGe aGdChdi Cf fbWY GdcdGe (B, (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\313s
(3gOjI GdYGQajf (B1\107s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds